Development of real‐time fluorescent reverse transcription loop‐mediated isothermal amplification assays for rhinovirus detection. Issue 7 (22nd February 2019) - Nakauchi, Mina; Takayama, Ikuyo; Takahashi, Hitoshi; Semba, Shohei; Saito, Shinji; Kubo, Hideyuki; Kaida, Atsushi; Oba, Kunihiro; Nagata, Shiho; Odagiri, Takato; Kageyama, Tsutomu
Abstract: Human rhinoviruses (RVs) belong to the genus Enterovirus of the family Picornaviridae, and are classified into RV‐A, ‐B, and ‐C species. Two assays were developed to detect RVs by a real‐time fluorescent reverse transcription loop‐mediated isothermal amplification method: one was designed based on the 5′‐untranslated regions (UTRs) of RV‐A and ‐B, and the other was designed based on the 5′‐UTR of RV‐C. The competence of both assays for the diagnosis of RV infection was tested using isolated viruses and compared with real‐time reverse transcription polymerase chain reaction assays on clinical specimens. Neither assay demonstrated cross‐reactivity with other tested enteroviruses, and they detected 19 out of 21 tested RV‐As and seven out of eight tested RV‐Cs. The specificity of the assays was 100% for the detection of RVs and their sensitivity for RV‐A and RV‐C was 86.3% and 77.3%, respectively, on clinical specimens by the combined use of both assays. Considering that both developed assays were highly specific and detected the majority of recently circulating RVs, they are helpful for the diagnosis of RV infection. Consequently, the results generated by these assays will enhance the surveillance of respiratory illness and the study of the roles of RVs associated with clinical features and disease severity.